(3efLjI GHf NdOhf GdJGQjNjI (B/s - (3GdWGdHj, eMeOs ((3dHfGf (B:s (3OGQ GdMOGKI ,s, 1981)
(3Gf GHf NdOhf aj GdMbjbI de jcf eDQNG eMJQaG h Gf GfWdb ef ThGZd JGQjNjI h SLd GMjGfG eG TGgOg HObI Jahb eG HdZfG Yf WQjb ZjQg h Gf OYGA JhbO PcGFg Gdi Gdfbd Yef GZadg ef SHbg aj HYV GdMGdGJ h cGf eYLHG HJGQjNg Pdc Gf geg aj GdfgGjI de jcf aj s
Keywords: (3YGdes; (3GHf NdOhfs